Severe neonatal enterovirus infection in twins with different outcomes: A case report - Storm, Kelly K.; De Herdt, Daan; Couderé, Karen; Verweij, Jaco J.; , VIRO-TypeNed; Torn, Leo; Hundscheid, Tim; van Wering, Herbert M. (Frontiers in Pediatrics, 2023)
Enteroviruses are among the most common causes of acute viral illness worldwide, and in neonates, the clinical course of these infections is rather heterogeneous. Severe complications, such as myocarditis, are associated with high mortality rates. In this case report, we present the clinical course of premature twins born at 35 weeks gestational age, suffering from a severe neonatal enterovirus infection with cardiac involvement which was fatal in one of the twins. This course led to prompt identification in the other twin, and facilitated the timely transfer to a neonatal intensive care unit with neonatal hemodynamic expertise, with prompt availability of ECMO would it have been indicated. Early supportive therapy in the other twin contributed in a positive outcome. Therefore, we emphasize the importance of early recognition in averting adverse consequences. As a recommendation, we propose routine screening of enterovirus in viral panels for febrile newborns.